2013
DOI: 10.1177/2150135113485760
|View full text |Cite
|
Sign up to set email alerts
|

Subaortic Membrane and Aorto-Septal Angle

Abstract: Background: Development of a subaortic membrane is not fully understood. Recurrence after surgical removal continues to be high. We sought to assess the differences in aorto-septal angles (AoSA) to possibly explain alterations within the left ventricular outflow tract, hence in subaortic membrane formation. Methods: A total of 113 patients who underwent subaortic membrane resection were matched by age and sex with 113 controls. The subaortic membrane resection group included isolated subaortic membranes (n ¼ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…It should be noted that visually, this variation in the angle is not very large, as demonstrated in Figure 6. Our results are in agreement with previous studies, reporting the normal LVOT angle range in adults to be between 126 and 144 degrees [10], and between 122 and 135 degrees [11], albeit with somewhat different methodology. This difference in methodology makes it difficult to compare the LVOT angle mea ured in adults to that in fetuses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that visually, this variation in the angle is not very large, as demonstrated in Figure 6. Our results are in agreement with previous studies, reporting the normal LVOT angle range in adults to be between 126 and 144 degrees [10], and between 122 and 135 degrees [11], albeit with somewhat different methodology. This difference in methodology makes it difficult to compare the LVOT angle mea ured in adults to that in fetuses.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also revealed that the LVOT angle of patients with AS was more obtuse than found in normal fetuses. This trend was similar to the results reported for an adult population with subaortic membranes compared to normal controls, ~127° vs. 137°, respectively [ 10 ]. AS may be caused by abnormal aortic valve or subaortic stenosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Risk factors promoting initial occurrence include morphological LVOT abnormalities such as sharp aortoseptal angle (AoSA), subphysiologic aortic annulus diameter, and large aortic valve-mitral valve separation distance ( 12 , 16 , 20 , 21 ). Recurrence, which occurs in 8–34% of patients over a 10 year period ( 12 , 22 27 ), has been associated with young age at both initial diagnosis and surgical intervention, smaller aortic annulus, proximity of the obstruction to the aortic valve, and a higher preoperative peak LVOT gradient ( 4 , 14 , 16 , 25 ).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A decrease in AoSA from 130 • to 110 • was accompanied by up to 23% and 69% increase in TSM and TSG, respectively. Given the wide range of AoSA values reported in the literature (Kleinert and Geva, 1993;Yap et al, 2008;Barboza et al, 2013), more dramatic mechanical stress alterations might be expected in some cases. In contrast, the steepening of the AoSA did not alter the oscillatory characteristics of the WSS, as suggested by the relatively similar OSI values predicted by the N-LV and S-LV models.…”
Section: Aosa Steepening Subjects the Septal Wall To Wss Overloadsmentioning
confidence: 99%